Cobalt-chromium alloys in fixed prosthodontics in Sweden - Maria Kassapidou; Victoria Franke Stenport; Lars Hjalmarsson; Carina B. Johansson (Taylor & Francis Group, 2017)
Aim: The aim of this study was to compile the usage of Co-Cr alloys in fixed prosthodontics (FP) among dental laboratories in Sweden. Methods: From March to October 2015, questionnaires were sent to 542 registered dental laboratories in Sweden. The questionnaires were divided in two parts, one for fixed dental-supported prosthodontics (FDP) and one for fixed implant-supported prosthodontics (FIP). Reminders were sent three times. Results: In total of 542 dental laboratories, 55% answered the questionnaires. Most dental laboratories use Co-Cr in FP, 134 (74%) in FDP and 89(66%) in FIP. The laboratories used Co-Cr alloys of various compositions in the prostheses, 35 for FDP and 30 for FIP. The most commonly used Co-Cr alloys for tooth-supported FDPs were (a) Wirobond® 280, (b) Cara SLM and (c) Wirobond® C. For implant-supported frameworks the frequently used alloys were: (a) Cara SLM, (b) Cara Milled and (c) Wirobond® 280. Except for the difference in composition of these alloys, they were also manufactured with various techniques. In tooth-supported prostheses the dominating technique was the cast technique while newer techniques as laser-sintering and milling were more commonly reported for implant-supported constructions. A fourth technique; the 'pre-state' milling was reported in FDP. Conclusion: More than 30 different Co-Cr alloys were reported as being used in FP. Thus, there is a need for studies exploring the mechanical and physical behavior and the biological response to the most commonly used Co-Cr alloys.